2015
DOI: 10.3892/mmr.2015.3922
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the expression of HDGF attenuates malignant biological behaviors of hilar cholangiocarcinoma cells

Abstract: Hepatoma-derived growth factor (HDGF) has been reported to be a potential predictive and prognostic marker for several types of cancer and important in malignant biological behaviors. However, its role in human hilar cholangiocarcinoma remains to be elucidated. Our previous study demonstrated that high expression levels of HDGF in hilar cholangiocarcinoma tissues correlates with tumor progression and patient outcome. The present study aimed to elucidate the detailed functions of the HDGF protein. This was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Studies have demonstrated that high HDGF expression is a novel prognostic factor in several types of tumour, including gall bladder cancer (32), endometrial carcinoma (33) and cholangiocarcinoma (34). In the present study, HDGF was found to be highly expressed in LADC tissues by immunohistochemical staining, and these levels were associated with N classification, lymph node metastasis and AJCC clinical stage.…”
Section: Discussionsupporting
confidence: 63%
“…Studies have demonstrated that high HDGF expression is a novel prognostic factor in several types of tumour, including gall bladder cancer (32), endometrial carcinoma (33) and cholangiocarcinoma (34). In the present study, HDGF was found to be highly expressed in LADC tissues by immunohistochemical staining, and these levels were associated with N classification, lymph node metastasis and AJCC clinical stage.…”
Section: Discussionsupporting
confidence: 63%
“…33 Thus, it is consistent that NUDC upregulation is associated with cell proliferation in ADAR1 over-expressed cells. Finally, HDGF is reported to be a predictive and prognostic marker for several types of cancer 34 and overexpressed in ovarian cancer cell lines. 35 HDGF is also shown to stimulate proliferation of hepatoma cells in vitro.…”
Section: The Pcna Interaction Network Mediated By Adar1 Overexpressionmentioning
confidence: 99%